On best‐fit corotated frames for 3D continuum finite elements. (28th January 2014) - Mostafa, M.; Sivaselvan, M.V.
SUMMARY We discuss a strategy to construct corotated frames for three‐dimensional continuum finite elements by minimizing deformations within the frame. We find that irrespective of the type of element and the number of nodes, using a quaternion parametrization of rotations, this minimization is naturally stated as computing the smallest eigenvalue of a 4 × 4 matrix. The simplicity of this smallest eigenvalue plays a crucial role when linearizing the kinematics. Ensuant quaternion algebra, although lengthy, results in remarkably simple formulas for projections that arise in the linearized kinematics. The exact stiffness matrix does not require computation of the second derivative of the rotation function and is also given by a simple formula. As a result, the implementation of this corotational formulation becomes particularly straightforward. Furthermore, in contrast to other results in the literature, the stiffness matrix for elements with translational DOFs is symmetric. For illustration, this corotational formulation is applied to a solid‐shell finite element, and numerical results are presented. Copyright © 2014 John Wiley & Sons, Ltd.